THE EFFECT OF LED LIGHT ON PRODUCTION OF FEMALE FLOWERS IN CUCUMER (CUCUMIS SATIVUS L.) - Riadi, Muhammad Fahri; Esyanti, Rizkita Rachmi; Faizal, Achmad (MATTER: International Journal of Science and Technology, 2015)
Light quality is one of the main factors that affect the productivity of cucumber plants, especially in induction of flowers. In this study, two lines of cucumber (Mercy and KE 27187) were treated with red (R), blue (B) and yellow (Y) light provided by LED (light emitting diode) with different compositions; RB (80:20) and RBY (80:10:10) for 8 h. Control plants were incubated under HPS lamps and TLD. The results showed that treatment of RB8 generate higher biomass and growth rate compared with RBY in both cucumber lines. Interestingly, RBY light increased sucrose content in plants, which positively correlate to the number of their female flowers. However, the energy efficiency of plants treated under LED light remains a major obstacle compared with control plants. Therefore, further research using appropriate PAR and light intensity of LEDs is needed to increase the productivity of female flowers in cucumbers.